Beliefs in the Dietary Benefits of Water Monitor, Varanus salvator Meat in Western Java, Indonesia - Evy Ayu Arida; Elika Boscha; Muhammad Alif Fauzi; Ari Ardiantoro; Noor Laina Maireda (Journal of Tropical Ethnobiology, 2021)
Local knowledge on the benefits of wild meat is probably the motivation behind consumption of such unusual source of protein. Various tribes in Indonesia are known to include wild meat of monitor lizards, Varanus spp. in their diet for several reasons including health benefits. Water monitor, Varanus salvator, is widely distributed across the Indonesian Archipelago and commonly found even in degraded habitats. Meat and internal organs of this species are commonly known to be consumed in Indonesia by at least three ethnics, i.e. Batak on Sumatra, Dayak on Kalimantan, and Minahasa on Sulawesi islands. We aim to investigate consumption of water monitor meat in a few communities in the western part of Java, where there is likely a custom albeit benign. Previous observations in the province of West Java showed consumption of a smaller scope in Sundanese communities, where religious background is of a restriction. Consumption of water monitor meat all over on Java seemed to be infrequent, yet also prevailing at a level of small business. In the western part of Java, consumption and sales seemed to be dominant in the northern areas, but mostly in Jakarta than in the regencies of West Java province. Direct observations and casual interviews with a few associates in West Java revealed a long-term practice in Cibinong. Besides its gastronomic benefit, meat of water monitor is believed as health tonic for men and a therapeutic method to treat skin diseases.